2019
DOI: 10.1016/j.eurox.2019.100084
|View full text |Cite
|
Sign up to set email alerts
|

The role of omentectomy in the surgical treatment of uterine serous carcinoma

Abstract: Objective The aims of this study were to assess the role of omentectomy in the staging of uterine serous carcinoma (USC) and to evaluate its impact on patient outcomes. Study design Patients diagnosed with USC at the First Affiliated Hospital of Sun Yat-sen University of China were retrospectively reviewed. The clinicopathological characteristics and survival data of 187 patients were analyzed. Risk factors for omental metastasis were evaluated. Kaplan–Meier survival cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…The reported overall rate of positive lymph nodes in EC was 5-9% in the entire cohort and 20-29% in the high-risk group [51,52]. Among the patients with positive lymph nodes, about a half had both pelvic and para-aortic involvement [60].…”
Section: Lymph Node Dissection In Ecmentioning
confidence: 97%
“…The reported overall rate of positive lymph nodes in EC was 5-9% in the entire cohort and 20-29% in the high-risk group [51,52]. Among the patients with positive lymph nodes, about a half had both pelvic and para-aortic involvement [60].…”
Section: Lymph Node Dissection In Ecmentioning
confidence: 97%
“…However, recent publications have shown that the detection of microscopic disease in normal-appearing omentum is rare in uterine serous carcinoma. 21 Although a recent study showed that the occurrence of omental metastases in patients with serous intraepithelial carcinoma varied from 5.1% to 9.8%, 22 adnexal involvement was found to be an important risk factor associated with omental involvement. 22 Hui et al also showed that when the omentum is involved, it is usually macroscopic disease or there is evidence of metastases elsewhere.…”
Section: Study Strengths and Weaknessesmentioning
confidence: 98%
“…21 Although a recent study showed that the occurrence of omental metastases in patients with serous intraepithelial carcinoma varied from 5.1% to 9.8%, 22 adnexal involvement was found to be an important risk factor associated with omental involvement. 22 Hui et al also showed that when the omentum is involved, it is usually macroscopic disease or there is evidence of metastases elsewhere. 23 Implications for Practice and Future Research Although this study was not meant to be a thorough literature review, we identified the largest studies on endometrial carcinoma limited to a polyp or the endometrium.…”
Section: Study Strengths and Weaknessesmentioning
confidence: 98%
“…It is suggested, though, that cytology of the peritoneal fluid should not be routinely performed, as positive results could be attributed to uterus handling. For some high-grade histological types of non-endometrioid EC, such as clear cell or serous carcinoma, and carcinosarcoma, omentectomy should be included in the surgical procedure, as visual assessment of the omentum appears to be insufficient [ 1 , 49 , 50 ]. When complete or optimal cytoreduction is attained, OS and progression-free survival (PFS) appear to be longer [ 51 ].…”
Section: Management Of Endometrial Cancermentioning
confidence: 99%